The Role of Muscle in Insect Energy Homeostasis - Bretscher, Heidi; O’Connor, Michael B. (Frontiers in Physiology, 2020)
Maintaining energy homeostasis is critical for ensuring proper growth and maximizing survival potential of all organisms. Here we review the role of somatic muscle in regulating energy homeostasis in insects. The muscle is not only a large consumer of energy, it also plays a crucial role in regulating metabolic signaling pathways and energy stores of the organism. We examine the metabolic pathways required to supply the muscle with energy, as well as muscle-derived signals that regulate metabolic homeostasis.